SKRINING FITOKIMIA EKSTRAK ETANOL RUMPUT LAUT GRACILARIA SP. ASAL DESA NEUSU KABUPATEN ACEH BESAR - Bhernama, Bhayu Gita (Department of Chemistry, Faculty of Science and Technology, UIN Ar-Raniry, 2020)
Gracilaria, sp is one type of red algae that produces jelly. Gracilaria, sp. are easily found in Indonesian waters so that they can be developed as aquaculture businesses, especially alongside the east coast of Indonesia. Gracilaria sp. has a secondary metabolic bioactive compound that can be used as a source of emulsifiers, thickeners, stabilizers, and also as medicines. Therefore, phytochemical screening of secondary metabolite compounds, among others, alkaloids, flavonoids, saponins, and terpenoids was carried out. The results showed a positive phytochemical screening of flavonoid compounds, terpenoids, and saponins in the Gracilaria seaweed.